My secretly hot husband. 5 - Jungyeon; Jungyeon; Nam, Gabi (Ize Press, 2025)
"Letitia continues her battle with Mephistel for the souls of thousands of residents of Abados. The goal--gather more zealous followers than the opponent! Once she realized that it's quite similar to being an online influencer, Letitia does quite well at her new stint as a cult leader, almost a bit too well..."--